Yoga and you Energizing and Relaxing Yoga for New and Experienced Students - Myers, Esther (Boston, MA Shambhala, 1997)
Whether you are new to yoga, returning to it, or want to enhance an on-going practice, Yoga and You is an invaluable companion on your journey. Esther Myers, one of Canada's leading yoga teachers, brings more than twenty years of teaching experience to help you integrate this ancient wisdom into contemporary life.
With clear step-by-step instructions for over one hundred poses and with photographs and illustrations throughout, Yoga and You guides you from relazation and breathing techniques through a comprehensive set of poses, including the most basic as well as advanced and challenging positions. Filled with helpful hints and tips, Yoga and You provides ideas for adapting the poses to your needs and abilities. Also included are suggested practice sequences for students of all levels.
1- Yoga and its roots
2- On the way
3- Your parctice
4- From the beginning: basic prnciples
5- Deep relaxation: Letting go
6- Pranayama: attention to your breath
7- Learning to stand
8- Simple stretches
9- Sun salutation: the wave
10- Standing poses
11- inverted poses and arm balances
12- Backbends
13- Sitting poses and forword bends
14- Sitting twists
15- Suggested practic sequences
Keywords: Hatha yoga - Popular works